Significantly improved photocatalytic activity of the SnO2/BiFeO3 heterojunction for pollutant degradation and mechanism. Issue 10 (15th May 2022) - Marwat, Mohsin Ali; Ullah, Habib; Usman, Muhammad; Ehsan, Muhammad Ali; Zhang, Haibo; Khan, Muhammad Fawad; Ali, Sher; Yousaf, Muhammad
Abstract: Herein, motivated with narrow/wide-bandgap heterojunction materials as one of the perfect solutions, we separately synthesized BiFeO3 (BFO) and SnO2 nanoparticles; then coupled them in various weight percentages to obtain nanocomposites with efficient contacts for visible light 2, 4-DCP and RhB degradation and effectively reduced charge recombination. The material of interest, i.e., with six weight percentage coupling of SnO2 (i.e., 6SO/94BFO), endorsed superior photoactivity for 2, 4-DCP and RhB degradation. In addition, under the visible light irradiation, this photocatalyst degraded 87.2% of RhB and 65.1% of 2, 4-DCP in 2h, which compared to pristine BiFeO3 nanoparticles are about 2.6- and 2.7-times enhancements, respectively. The photoluminescence spectroscopy and mechanism model showed a substantial interface between BiFeO3 and SnO2 and unfeasible electron-holes recombination. The electrons and holes are entirely utilized to produce superoxides and OH radicals, respectively, predicting enhanced visible-light photodegradation. Overall, this work offers novel narrow/wide-bandgap heterojunction nanocomposites as feasible aspirants for pollution control and effective visible light photodegradation of chlorinated compounds.